(Re)configurações do feminino na Trilogia da Solidão, de Patricia Bins - Mendes, Marta Freitas (2019)
The present dissertation is an analysis of how femininity is featured in Trilogia da Solidão (“The Trilogy of Solitude”, free translation), composed of Patricia Bins’ novels Jogo de fiar (1983), Antes que o amor acabe (1984), and Janela do sonho (1986), emphasizing its female characters, narrator and narrative space, which are central narrative categories to comprehend the trilogy through the approach of female-authored literature. The main question to be answered is: how does femininity figure and refigure throughout the Trilogy? The protagonists Ara (Jogo de fiar), Anna (Antes que o amor acabe) e Maria (Janela do sonho) are women who turn to writing in order to rescue and rewrite their lives, by assuming the task of breaking the silence about themselves. In this trilogy, Bins generates an own narrative word, starting from subjects such as solitude, marriage, motherhood, writing and female condition. The first part of this study reviews key-concepts to then develop the analysis, elucidating the meanings of literature, literary narrative, elements of narrative and the novel, according to Bakhtin (1993), Reis (2003), Bachelard (1978), Forster (2005), Friedman (2002) e Borneuf & Ouellet (1976), among others. The second chapter locates and comments the femininity issue, as well as women’s literature, starting from essential authors, as Beauvoir (1980), Woolf (2014; 2017), Schmidt (1988; 1995) e Richard (2002); in addition it presents a reflexive analysis of Bins’ work and where her work is placed inside Brazilian and SouthBrazilian culture. The last chapter is divided in three sections, each dedicated to one of the three books that compose “The Trilogy of Solitude”, chronologically, following the course of each protagonist: Ara, Anna and Maria, focusing on selected narrative elements to, at last, approach how femininity is represented in these works. Finally, we present the final considerations, followed by references and annex, which include the catalog of the major publications that constitute the literary criticism on Patricia Bins’ works